Multifilter Transit Observations of WASP-39b and WASP-43b with Three San Pedro Mártir Telescopes. (4th January 2016) - Ricci, D.; Ramón-Fox, F. G.; Ayala-Loera, C.; Michel, R.; Navarro-Meza, S.; Fox-Machado, L.; Reyes-Ruiz, M.; Sevilla, S. Brown; Curiel, S.
Abstract: Three optical telescopes located at the San Pedro Mártir National Observatory were used for the first time to obtain multifilter defocused photometry of the transiting extrasolar planets WASP-39b and WASP-43b. We observed WASP-39b with the 2.12 m telescope in the U filter for the first time, and additional observations were carried out in the R and I filters using the 0.84 m telescope. WASP-43b was observed in VRI with the same instrument, and in the i filter with the robotic 1.50 m telescope. We reduced the data using different pipelines and performed aperture photometry with the help of custom routines in order to obtain the light curves. The fit of the light curves (1.5-2.5 mmag rms), and of the period analysis, allowed a revision of the orbital and physical parameters, revealing for WASP-39b a period (4.0552947 ± 9.65 × 10 -7 days) which is 3.084 ± 0.774 seconds larger than previously reported. Moreover, we find for WASP-43b a planet/star radius (0.1738 ± 0.0033) which is 0.01637 ± 0.00371 larger in the i filter with respect to previous works, and that should be confirmed with additional observations. Finally, we confirm no evidence of constant period variations in WASP-43b.